Preparation method and application of ruthenium-doped nickel dimethylglyoxime nano array composite structure material taking foamed nickel as substrate
By growing a ruthenium-doped nickel dimethylglyoxime nanoarray in situ on a nickel foam substrate, a three-dimensional nanoarray structure is formed, which solves the problem of expensive precious metal catalysts and realizes efficient and stable catalysis of oxygen evolution reaction in water electrolysis, making it suitable for industrial applications.
Patent Information
- Application Number
- CN202411690880.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-25
- Publication Date
- 2025-01-07
AI Technical Summary
Existing precious metal oxide catalysts are limited in their application in the oxygen evolution reaction of water electrolysis due to their high cost and scarcity, and nickel-based catalysts require improvements in their electronic structure and surface properties to enhance their catalytic performance.
Ruthenium-doped dimethylglyoxime nickel nanoarray composite material was prepared on a nickel foam substrate using an in-situ growth method. Through hydrothermal reaction and ultrasonic treatment, a three-dimensional sheet-like nanoarray structure was formed, which can be used as a catalyst for the oxygen evolution reaction of water electrolysis.
It significantly reduces the overpotential of the oxygen evolution reaction, improves catalytic activity and stability, reduces the external voltage requirement, is suitable for large-scale industrial production, and the synthesis process is simple and safe.
Smart Images

Figure CN119265629A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of material science and technology and electrocatalysis technology, and specifically relates to a preparation method and application of a ruthenium-doped diacetyl oxime nickel nano-array composite structure material based on nickel foam. Background Art
[0002] Due to the limited reserves of fossil energy and the environmental pollution caused by combustion, energy issues have become a major problem that human society needs to solve urgently. Electrocatalytic water splitting provides a sustainable strategy to provide clean energy through cathode hydrogen evolution reaction and anode oxygen evolution reaction. For the electrolytic water oxygen evolution reaction, it is kinetically unfavorable due to the multiple steps of proton-coupled electron transfer, so effective catalysts are essential. So far, precious metal oxides, such as ruthenium dioxide and iridium dioxide, have shown high performance in the catalysis of electrolytic water oxygen evolution reaction. However, the high price and scarcity of these precious metals seriously hinder their practical application. Therefore, there is an urgent need to develop new catalysts with low prices and excellent performance.
[0003] Nickel-based oxygen evolution electrocatalysts have a wide range of applications in energy conversion and storage, especially in the fields of water splitting and fuel cells. In recent years, researchers have designed and optimized nickel-based catalysts through a variety of strategies to improve their catalytic performance. A common strategy is to use element doping to optimize the electronic structure and surface properties of nickel-based catalysts. For example, by introducing rare earth elements such as lanthanum or yttrium, the band structure of nickel-based catalysts can be adjusted and their electrocatalytic activity can be enhanced. At the same time, doping with metal elements such as palladium or gold can also improve the conductivity and catalytic activity of nickel-based catalysts. Another strategy is to prepare nickel-based catalysts with specific morphologies and structures. For example, researchers have successfully prepared nickel-based catalysts with different morphologies such as nanosheets, nanorods, nanotubes and nanoflowers. These nickel-based catalysts with different morphologies exhibit different catalytic properties.
[0004] However, among nickel-based catalysts, there are no reports of ruthenium-doped catalysts based on dimethylglyoxime nickel. Compared with traditional nickel-based catalysts, the in-situ grown dimethylglyoxime nickel substrate has a simpler preparation method and exhibits a nanosheet microscopic morphology, which is conducive to increasing the surface area and active sites of the catalyst. By regulating the specific synthesis conditions, the thickness and interlayer spacing of dimethylglyoxime nickel nanosheets can be controlled, further improving its structure and performance. The electrochemical performance of in-situ grown dimethylglyoxime nickel doped with ruthenium is more significantly improved, and it has ultra-long stability under large currents. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for synthesizing a ruthenium-doped dimethylglyoxime nickel nano-array composite structure material with nickel foam as a substrate grown in situ. The method comprises the following steps: using a nickel foam sheet as an electrode material and a reaction template, pretreating the nickel foam sheet, and then growing a dimethylglyoxime nickel nano-array composite structure on the surface of the nickel foam sheet under relatively mild conditions by utilizing a hydrothermal reaction. Finally, ultrasonic growth is used to obtain a ruthenium-doped dimethylglyoxime nickel nano-array composite structure as a catalytic active center for electrolytic water oxygen evolution reaction, and the composite structure is closely combined with the electrode material nickel foam sheet. The nickel foam sheet on which the ruthenium-doped dimethylglyoxime nickel nano-array composite structure is grown is placed in an electrochemical three-electrode system as an electrolytic water oxygen evolution electrode.
[0006] Therefore, one of the purposes of the present invention is to provide a method for in-situ growth of a ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam, and the specific operation is as follows:
[0007] (1) Pretreatment of the nickel foam sheet: firstly, the nickel foam sheet is placed in hydrochloric acid for ultrasonic treatment, then the nickel foam sheet treated with hydrochloric acid is carefully ultrasonically cleaned with anhydrous ethanol and deionized water to remove impurities on the surface of the nickel foam sheet, and finally, the nickel foam sheet is placed in an oven at 60-80° C. for drying for 40-60 minutes;
[0008] (2) Preparation of reaction solution: dissolve dimethylglyoxime in ethanol solution at a ratio of 1 mmol:20 ml, and dissolve nickel chloride hexahydrate in ultrapure water at a ratio of 0.5 mmol:20 ml. Stir the two solutions at room temperature for 30 minutes under the action of a magnetic force to uniformly disperse the drugs in the solution. Mix 10 ml of each of the two stirred solutions and continue stirring at room temperature for 20 minutes under the action of a magnetic force to obtain a final reaction solution.
[0009] (3) transferring the nickel foam sheet pretreated in step (1) and the final reaction solution in step (2) into a 40 ml polytetrafluoroethylene liner, placing the reactor in an oven at 200° C. after a hydrothermal reaction for 6 hours and then cooling to room temperature naturally;
[0010] (4) taking the reactor out of the oven, taking the nickel foam sheet out of the completely cooled tetrafluoroethylene liner, washing it with ethanol and deionized water alternately for multiple ultrasonic washes, and finally heating it in a vacuum oven at 150° C. for 12 hours to obtain a diacetyl oxime nickel sheet with nickel foam as the substrate;
[0011] (5) placing the nickel foam-based dimethylglyoxime nickel sheet obtained in step (4) in 8 ml of a 1.5 mg / mL ruthenium chloride solution and continuously ultrasonicating for 6 hours; after the ultrasonication is completed, taking out the nickel foam-based dimethylglyoxime nickel sheet from the ruthenium chloride solution, ultrasonically washing it with ethanol and deionized water alternately for multiple times, and finally drying it in a vacuum oven at 40° C. for 6 hours to obtain a ruthenium-doped dimethylglyoxime nickel nanoarray composite structure material based on nickel foam.
[0012] Wherein, the step (1) of pretreating the nickel foam sheet is as follows: firstly, cutting the nickel foam sheet into 1 cm×2 cm pieces, ultrasonically acidifying and activating the nickel foam sheet in 1 mol / L hydrochloric acid for 20 minutes, then ultrasonically treating the nickel foam sheet in anhydrous ethanol for 1-5 minutes, taking the nickel foam sheet out and repeatedly rinsing it with deionized water, and ultrasonically cleaning the nickel foam sheet in deionized water for 3-5 minutes; and finally drying the nickel foam sheet in a 60-80° C. oven for 40-60 minutes.
[0013] Wherein, in the final reaction solution of step (2), the concentration of nickel chloride hexahydrate is 0.025 mol / L, and the concentration of dimethylglyoxime is 0.0125 mol / L.
[0014] The ruthenium chloride solution in step (5) is prepared as follows: 12 mg:8 ml of ruthenium chloride is dissolved in ultrapure water, and ultrasonicated for 10 minutes to fully dissolve it, thereby obtaining a ruthenium chloride solution.
[0015] In the present invention, the multiple ultrasonic washing times refer to 4-6 times.
[0016] In the present invention, step (1) uses hydrochloric acid ultrasonic treatment on the nickel foam substrate to remove impurity elements and oxide layer on the substrate, and uses deionized water and ethanol solution to remove residual hydrochloric acid and impurities remaining on the surface of the substrate. The specific molar ratio mentioned in step (2) is the optimal ratio, which conforms to the reaction chemical formula of the two elements. After 6 hours of reaction at 200° C. in step (3), the reaction intermediate product Ni2Cl(OH)3 is obtained. In step (4), the intermediate product Ni2Cl(OH)3 is washed several times to remove surface impurities and residual drugs, and then after 12 hours of reaction at 150° C., the next intermediate product dimethylglyoxime nickel is obtained. In step (5), the concentration of 1.5 mg / mL of ruthenium chloride solution and the ultrasonic reaction time of 6 hours are both the optimal ratios.
[0017] The second object of the present invention is to provide a ruthenium-doped diacetyl oxime nickel nanoarray composite structure material with nickel foam as the substrate, which is prepared by the above method and has a three-dimensional sheet-like nanoarray structure.
[0018] The third object of the present invention is to provide an application of the above-mentioned ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam as a catalyst for oxygen evolution reaction in water electrolysis, which significantly reduces the overpotential of the oxygen evolution reaction, has good stability, exhibits excellent catalytic activity for oxygen evolution reaction in water electrolysis, and has good application prospects.
[0019] The fourth object of the present invention is to provide an electrode for oxygen evolution by electrolysis of water. The ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam is placed in an electrochemical three-electrode test system as an electrode for oxygen evolution by electrolysis of water. In an alkaline medium, the oxygen evolution reaction by electrolysis of water can be carried out efficiently at a lower applied voltage and has good stability.
[0020] Compared with the prior art, the present invention has the following beneficial technical effects:
[0021] 1. The present invention utilizes an in-situ growth method to synthesize a ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam as a catalyst for the electrolytic water oxygen evolution reaction, so that the catalyst and the electrode material can be closely combined, which not only solves the problem of poor conductivity of the hydroxide, but also promotes charge transfer.
[0022] 2. The present invention utilizes the three-dimensional pore structure of the reaction substrate to in situ synthesize a three-dimensional sheet-like nanoarray structure with a large specific surface area, which greatly increases the catalytic active sites of the catalyst, so that the oxygen evolution electrode can catalyze the electrolysis of water and oxygen evolution reaction efficiently at a lower applied voltage and has good stability. Specifically, at 100 mA cm -2 It has a lower overpotential (308 mV), exceeding that of most reported nickel-based electrocatalysts.
[0023] 3. The synthesis process of the present invention is simple, fast and easy to control. It does not produce highly dangerous intermediates, does not require complex or high-tech processes, does not require external binders, and the required raw materials are widely available and inexpensive.
[0024] 4. The present invention has a significant effect on saving energy consumption and improving efficiency in the electrolytic water oxygen evolution reaction. It is a green, safe, efficient, simple and mature synthesis process. At the same time, it can achieve large-scale preparation, is suitable for large-scale industrial production, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 This is a picture of the actual ruthenium-doped diacetyl oxime nickel nanoarray composite structure material with a size of 1cm×2cm and based on nickel foam.
[0026] Figure 2 This is a scanning electron microscope image of the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam in Example 1;
[0027] Figure 3 This is the XRD pattern of the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam in Example 1;
[0028] Figure 4 This is the Raman image of the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam in Example 1;
[0029] Figure 5 A schematic diagram of placing the ruthenium-doped dimethylglyoxime nickel nano-array composite structure material based on nickel foam in Example 1 in an electrochemical three-electrode test system as an electrode for electrolyzing water and evolving oxygen;
[0030] Figure 6 This is a graph showing the electrochemical performance of the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam prepared in Example 1;
[0031] Figure 7 This is a stability performance diagram of the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam in Example 1. DETAILED DESCRIPTION
[0032] The specific implementation of the present invention will be further described below in conjunction with the accompanying drawings.
[0033] Example 1
[0034] (1) Pretreatment of nickel foam sheet: First, cut the nickel foam sheet into a size of 1 cm×2 cm and place it in 1 mol / L hydrochloric acid for 20 minutes for ultrasonic treatment, then place it in anhydrous ethanol for ultrasonic treatment for 1-5 minutes, take it out and rinse it repeatedly with deionized water, and then place it in deionized water for ultrasonic cleaning for 3-5 minutes; finally, place it in a 60-80°C oven for drying for 40-60 minutes to remove impurities on the surface of the nickel foam sheet;
[0035] (2) Preparation of reaction solution: 1 mmol of dimethylglyoxime (DMG) was dissolved in 20 ml of ethanol solution, and 0.5 mmol of nickel chloride hexahydrate was dissolved in 20 ml of ultrapure water. The two solutions were stirred at room temperature for 30 minutes under the action of a magnetic force to make the drugs uniformly dispersed in the solution; 10 ml of each of the two stirred solutions was mixed, and the stirring was continued at room temperature for 20 minutes under the action of a magnetic force to obtain a final reaction solution;
[0036] (3) transferring the nickel foam sheet pretreated in step (1) and the final reaction solution in step (2) into a 40 ml polytetrafluoroethylene liner, placing the reactor in an oven at 200° C. after a hydrothermal reaction for 6 hours and then cooling to room temperature naturally;
[0037] (4) taking the reactor out of the oven, taking the nickel foam sheet out of the completely cooled tetrafluoroethylene liner, ultrasonically washing it with ethanol and deionized water for multiple times, and finally heating it in a vacuum oven at 150° C. for 12 hours to obtain a diacetyl oxime nickel sheet with the nickel foam as the substrate;
[0038] (5) dissolving 12 mg of ruthenium chloride in 8 ml of ultrapure water, and ultrasonicating for 10 minutes to fully dissolve it to obtain a ruthenium chloride solution; placing the nickel foam-based dimethylglyoxime nickel sheet obtained in step (4) in the ruthenium chloride solution, and continuously ultrasonicating for 6 hours, taking it out after the ultrasonication is completed, ultrasonically washing it with ethanol and deionized water for multiple times, and finally drying it in a vacuum oven at 40°C for 6 hours to obtain a ruthenium-doped dimethylglyoxime nickel nanoarray composite structure material based on nickel foam.
[0039] The ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam is placed in an electrochemical three-electrode test system to serve as an electrode for oxygen evolution in water electrolysis.
[0040] Example 2
[0041] This embodiment is the same as embodiment 1, except that a 1cm×2cm carbon paper / cloth sheet is used instead of a nickel foam sheet as a substrate. Compared with embodiment 1, the growth effect of dimethylglyoxime nickel in embodiment 2 after hydrothermal treatment is worse. The electrochemical test results show that when other conditions remain unchanged, the overpotential difference is close to 200mv at a current density of 50mA when a carbon paper / cloth sheet is used instead of a nickel foam sheet as a substrate. The rough surface provided by the nickel foam substrate is not only more conducive to the growth of dimethylglyoxime nickel, but also helps the doping of ruthenium.
[0042] Example 3
[0043] This embodiment is the same as Example 1, except that the molar ratio of the DMG drug to the nickel chloride hexahydrate drug in the hydrothermal part is 1:1 or 1.5:1. The electrochemical properties of the samples prepared under these two conditions have a potential difference of more than 50mv compared with the potential under the optimal ratio of 2:1.
[0044] Example 4
[0045] The steps of this embodiment are the same as those of embodiment 1, except that the electrochemical performance of the ultrasonic growth part under the conditions of ultrasonic time of 1 hour, 3 hours, 9 hours and 12 hours respectively, and the potential difference of 1.496V under the optimal ultrasonic time of 6 hours ranges from 40 to 150mv.
[0046] Example 5
[0047] The steps of this embodiment are the same as those of embodiment 1, except that the electrochemical performance of the ultrasonic growth part under the conditions of ruthenium chloride solution concentrations of 0.1 mg / ml, 0.5 mg / ml, 1.0 mg / ml and 2 mg / ml respectively, the results show that except for the comparison sample with a ruthenium chloride solution concentration of 2 mg / ml, which exhibits a potential close to that of embodiment 1, the potential differences under the other three concentration conditions at a current density of 50 mA and that of embodiment 1 range from 30 to 100 mv, however, the potential difference between the comparison sample with a concentration of 2 mg / ml and embodiment 1 is around 10 mv, with no obvious improvement effect.
[0048] Depend on Figure 2 It can be seen that the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam prepared in Example 1 is a good sheet-like nanoarray structure with uniform size and uniform dispersion; the sheet-like array structure with a relatively smooth surface is Figure 2 Clearly visible in.
[0049] Depend on Figure 3 and Figure 4 It can be seen that the ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam prepared in Example 1 was successfully prepared, and its XRD pattern corresponds accurately to the standard PDF card, and the Raman pattern also presents corresponding characteristic peaks.
[0050] The electrochemical performance test of the ruthenium-doped dimethylglyoxime nickel nano-array composite structure material based on nickel foam prepared in Example 1 of the present invention as a catalyst for oxygen evolution reaction in electrolysis of water was carried out according to the following method:
[0051] 1) Using a three-electrode system, such as Figure 5 As shown, the ruthenium-doped dimethylglyoxime nickel nanoarray composite structure material based on nickel foam was directly used as the working electrode, the counter electrode was a platinum sheet electrode, and the saturated calomel electrode was used as the reference electrode. The electrochemical test was carried out on a Chenhua (CHI 760E) electrochemical workstation. The electrolyte was a 1 mol / L potassium hydroxide solution. Before the test, oxygen was introduced into the electrolyte for 30 minutes for saturation treatment, and the oxygen atmosphere was maintained during the test.
[0052] 2) Linear scanning voltammetry test: The scanning speed is 5 mV / s, and the electrode potential is converted to the reversible hydrogen electrode. The calculation formula is:
[0053] Overpotential = electrode potential + 0.059*pH + 0.2415-1.23 (V);
[0054] 3) Stability test: Apply 200mA / cm on the same electrode 2 The potential-time curve was recorded for 1100 hours at a current density of 1.5 %.
[0055] Electrochemical performance test Figure 6 , significantly reducing the overpotential of the oxygen evolution reaction, at 50mA / cm 2 At a current density of 200 mA / cm, the overpotential of the catalyst prepared in Example 1 was reduced by nearly 100 mV to only 1.496 V compared with the commercial ruthenium dioxide catalyst, and by nearly 120 mV compared with nickel diacetyl oxime. 2 The stability measured after the current density is Figure 7 It can be seen that the prepared ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam has excellent stability under large current. 2 The device can run stably for more than 1000 hours at a current density of 1.
Claims
1. A method for preparing an in-situ grown ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam, characterized in that: The specific steps include: (1) Pretreatment of the nickel foam sheet: firstly, the nickel foam sheet is placed in hydrochloric acid for ultrasonic treatment, then the nickel foam sheet treated with hydrochloric acid is carefully ultrasonically cleaned with anhydrous ethanol and deionized water to remove impurities on the surface of the nickel foam sheet, and finally, the nickel foam sheet is placed in an oven at 60-80° C. for drying for 40-60 minutes; (2) Preparation of reaction solution: dissolve dimethylglyoxime in ethanol solution at a ratio of 1 mmol:20 ml, and dissolve nickel chloride hexahydrate in ultrapure water at a ratio of 0.5 mmol:20 ml. Stir the two solutions at room temperature for 30 minutes under the action of a magnetic force to uniformly disperse the drugs in the solution. Mix 10 ml of each of the two stirred solutions, and continue stirring at room temperature for 20 minutes under the action of a magnetic force to obtain a final reaction solution. (3) transferring the nickel foam sheet pretreated in step (1) and the final reaction solution in step (2) into a 40 ml polytetrafluoroethylene liner, placing the reactor in an oven at 200° C. after a hydrothermal reaction for 6 hours and then cooling to room temperature naturally; (4) taking the reactor out of the oven, taking the nickel foam sheet out of the completely cooled tetrafluoroethylene liner, washing it with ethanol and deionized water alternately for multiple ultrasonic washes, and finally heating it in a vacuum oven at 150° C. for 12 hours to obtain a diacetyl oxime nickel sheet with nickel foam as the substrate; (5) placing the nickel foam-based dimethylglyoxime nickel sheet obtained in step (4) in 8 ml of a 1.5 mg / mL ruthenium chloride solution and continuously ultrasonicating for 6 hours; after the ultrasonication is completed, taking out the nickel foam-based dimethylglyoxime nickel sheet from the ruthenium chloride solution, ultrasonically washing it with ethanol and deionized water alternately for multiple times, and finally drying it in a vacuum oven at 40° C. for 6 hours to obtain a ruthenium-doped dimethylglyoxime nickel nanoarray composite structure material based on nickel foam.
2. The method for preparing an in-situ grown ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam according to claim 1, characterized in that: The step (1) of pretreating the nickel foam sheet is as follows: firstly, cutting the nickel foam sheet into 1 cm×2 cm pieces, ultrasonically acidifying and activating the nickel foam sheet in 1 mol / L hydrochloric acid for 20 minutes, then ultrasonically treating the nickel foam sheet in anhydrous ethanol for 1-5 minutes, taking the nickel foam sheet out and repeatedly rinsing it with deionized water, and ultrasonically cleaning the nickel foam sheet in deionized water for 3-5 minutes; and finally drying the nickel foam sheet in an oven at 60-80° C. for 40-60 minutes.
3. The method for preparing an in-situ grown ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam according to claim 1, characterized in that: In the final reaction solution of step (2), the concentration of nickel chloride hexahydrate is 0.025 mol / L, and the concentration of dimethylglyoxime is 0.0125 mol / L.
4. The method for preparing an in-situ grown ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam according to claim 1, characterized in that: The ruthenium chloride solution preparation scheme in step (5) is as follows: 12 mg: 8 ml of ruthenium chloride is dissolved in ultrapure water, and ultrasonicated for 10 minutes to fully dissolve it to obtain a ruthenium chloride solution.
5. The method for preparing an in-situ grown ruthenium-doped diacetyl oxime nickel nanoarray composite structure material based on nickel foam according to claim 1, characterized in that: The multiple ultrasonic washing times refer to 4-6 times.
6. A ruthenium-doped diacetyl oxime nickel nanoarray composite structural material based on nickel foam, prepared by the method described in any one of claims 1 to 5, having a three-dimensional sheet-like nanoarray structure.
7. Use of the ruthenium-doped dimethylglyoxime nickel nanoarray composite structure material based on nickel foam as claimed in claim 6 as a catalyst for oxygen evolution reaction in electrolytic water.
8. An electrode for oxygen evolution by water electrolysis, characterized in that: The ruthenium-doped diacetyl oxime nickel nano-array composite structure material based on nickel foam prepared by any of the methods described in claims 1-5 is placed in an electrochemical three-electrode test system and used as an electrode for electrolyzing water and oxygen evolution in an alkaline medium.